Host-specialized fibrinogen-binding by a bacterial surface protein promotes biofilm formation and innate immune evasion - Pickering, Amy C.; Vitry, Pauline; Prystopiuk, Valeriia; Garcia, Brandon L.; Höök, Magnus; Schoenebeck, Jeffrey; Geoghegan, Joan A.; Dufrêne, Yves F.; Fitzgerald, J. Ross (My University, 2019)
Fibrinogen is an essential part of the blood coagulation cascade and a major component of the extracellular matrix in mammals. The interface between fibrinogen and bacterial pathogens is an important determinant of the outcome of infection. Here, we demonstrate that a canine host-restricted skin pathogen, Staphylococcus pseudintermedius, produces a cell wall-associated protein (SpsL) that has evolved the capacity for high strength binding to canine fibrinogen, with reduced binding to fibrinogen of other mammalian species including humans. Binding occurs via the surface-expressed N2N3 subdomains, of the SpsL A-domain, to multiple sites in the fibrinogen α-chain C-domain by a mechanism analogous to the classical dock, lock, and latch binding model. Host-specific binding is dependent on a tandem repeat region of the fibrinogen α-chain, a region highly divergent between mammals. Of note, we discovered that the tandem repeat region is also polymorphic in different canine breeds suggesting a potential influence on canine host susceptibility to S. pseudintermedius infection. Importantly, the strong host-specific fibrinogen-binding interaction of SpsL to canine fibrinogen is essential for bacterial aggregation and biofilm formation, and promotes resistance to neutrophil phagocytosis, suggesting a key role for the interaction during pathogenesis. Taken together, we have dissected a bacterial surface protein-ligand interaction resulting from the co-evolution of host and pathogen that promotes host-specific innate immune evasion and may contribute to its host-restricted ecology.
Keywords: Fibrinogen; Tandem repeats; Host-pathogen interactions; Bacterial biofilms; Bacterial pathogens; Staphylococcus aureus; Binding analysis; Cell binding